The Existence of Industrial Relations Dispute Resolution Institutions at The Close of The Company (Lock Out) - Pamungkas, Yogo; Yurikosari, Andari; Amriyati, Amriyati (Green Publisher Indonesia, 2023)
The process of resolving industrial relations disputes in Indonesia can basically be carried out through bipartite followed by mediation or conciliation or arbitration and carried out with industrial relations courts. This normative settlement providesaway out with an orderly state. Industrial relations can arise due to several related matters such as: employment agreements, positive laws and differences in interests. The focus of the problem is whether the definition of the concept of industrial relations conflict has been clearly defined? Has the resolution of industrial relations conflicts been achieved? Is the purpose of closing the company achieved according to its legal objectives? Is the closure of the company to resolve industrial relations conflicts achieved? What limitations are there in court decisions in examining and resolving industrial relations disputes before or after the closure of a company? This study uses the systematic study method of verdict. The results showed that the closure of the company was not effective in resolving industrial relations conflicts